Retinoblastoma - Agnieszka Budny; Cezary Grochowski (Journal of Education, Health and Sport, 2018)
Retinoblastoma is a tumor originating from the nuclear layer of the primary retinal photoreceptor cells, genetically determined. It develops due to a mutation in chromosome 13 in the q14 band. It is the most common, originally malignant intraocular change in childhood and accounts for 10-15% of cancer cases occurring in the first year of life [1]. Usually this cancer manifests itself as a leukocoria in a child under two years of age. In a congenital form, it can be multifocal, on both sides, and the risk of secondary cancers should also be taken into account. Diagnosis of retinoblastoma requires indirect ophthalmoscopy and research using imaging diagnostics techniques: ultrasonography (USG), magnetic resonance imaging (MRI) or computed tomography (CT). If left untreated, it leads to metastasis and death of the child. With the advancement of medicine, survival with modern treatment methods is> 95%. More and more often it is possible to save the mutant eye enucleation surgery. Immediate referral to an ophthalmologist's oncologist and proper management by an interdisciplinary team are necessary to optimize the visual effect and survival [2].